2018
DOI: 10.1016/j.fct.2018.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro studies of the biological potential and chemical composition of stems, leaves and berries Aronia melanocarpa's extracts obtained by subcritical water extraction

Abstract: Comparative in vitro studies of the biological potential and chemical composition of stems, leaves and berries Aronia melanocarpa's extracts obtained by subcritical water extraction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 73 publications
5
66
0
Order By: Relevance
“…Nevertheless, the main phenolic acids quantified in black currant leaves were chlorogenic, neochlorogenic, cryptochlorogenic, and p-coumaric acids, with the most abundant being p-coumaric acid [8,10,20,21,26]. Rubus leaves were rich in ellagic acid and p-coumaric acid [12,19,23,28,29], while in aronia leaves, the highest levels of sinapic acid were identified [25]. Other authors stated that the main phenolic acids occurring in aronia leaves were chlorogenic, neochlorogenic, 3,4-dihydroxyphenylacetic, and protocatechuic acids [18,30] (Table 1).…”
Section: Phenolic Compoundsmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, the main phenolic acids quantified in black currant leaves were chlorogenic, neochlorogenic, cryptochlorogenic, and p-coumaric acids, with the most abundant being p-coumaric acid [8,10,20,21,26]. Rubus leaves were rich in ellagic acid and p-coumaric acid [12,19,23,28,29], while in aronia leaves, the highest levels of sinapic acid were identified [25]. Other authors stated that the main phenolic acids occurring in aronia leaves were chlorogenic, neochlorogenic, 3,4-dihydroxyphenylacetic, and protocatechuic acids [18,30] (Table 1).…”
Section: Phenolic Compoundsmentioning
confidence: 98%
“…These results were also confirmed by Teleszko and Wojdyło [10] in raspberry and aronia plants. Cvetanovic et al [25] compared the biological potential and chemical composition of extracts from the stems, leaves, and berries of A. melanocarpa and showed that the highest concentration of total phenolic compounds (131.53 mg of chlorogenic acid equivalent/g) and flavonoid (88.64 mg of rutin equivalent/g) was present in leaves, followed by stems and berries. Paunovic et al [8] showed that soil management systems had positive effects on the synthesis and accumulation of flavonols and flavan-3-ols in both berries and leaves of black currant and a positive influence on anthocyanin accumulation in leaves but not in berries.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…The popularity of A. melanocarpa is increasing due to its association with potential health benefits such as antioxidative, antibacterial, antiviral, antimutagenic, anticancer, cardioprotective, hepatoprotective, gastroprotective, antidiabetic, and anti-inflammatory activity which have been shown in in vitro and in vivo studies (Cvetanović et al, 2018;Kokotkiewicz, Jaremicz, & Luczkiewicz, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…e DPPH and ABTS assay offered a cost-effective, efficient, and rapid solution in evaluating antioxidant assay based on calculating percentage inhibition which is equivalent with antioxidant capacity content in the sample. ese applied methods are widely used in the evaluation of antioxidant abilities for both natural and synthetic molecules [30]. e smaller the concentration of antioxidants and the faster the antioxidant reacts with free radicals, the greater the scavenging activity [31].…”
Section: Total Antioxidant Capacity (Tac)mentioning
confidence: 99%